IMPLEMENTASI KEBIJAKAN WARISAN BUDAYA TAKBENDA (WBTB) INDONESIA - Marjanto, Damardjati Kun (Kebudayaan, 2016)
AbstractThe objectives of the research for policy of intangible cultural heritage (ICH) are as follow.(1) To understand the processes and problems of implementation of ICH policy in Indonesia; (2)To identify stakeholders involved in ICH policies that have been registered and confirmed; and(3) To ascertain a plan of action programs that carried out by relevant agencies following thedetermination of ICH policy in Indonesia. This study uses qualitative research method, throughinterviews and focus group discussion (FGD) to a number of informants, i.e. government officials,cultural actors, and community members. The implementation of the Minister of Education andCulture regulation that related to “the administrative procedures” of ICH policy has be done asgood as possible by Directorate of Values Internalization and Cultural Diplomacy. However, it isbelieved that the effort is still need to be improved. It seems that this is caused by poor technicalability for filling the form and misunderstanding about ICH, which often confused as havingthe same meaning and value with cultural heritage. Local stakeholders need to have the sameunderstanding about the importance of the regulation of president and of Ministry of Educationand Culture. Therefore, all the regions can carry out this policy together and contribute toeach other in protecting ICH through action programs. Bida’i, Songket, Sambas, and BetangTraditional House in West Kalimantan Province; and Makepung and Tektekan in Bali Provincehave been designated as ICH of Indonesia. However, conservation efforts should not stop at thisdetermination only.Keywords: Intangible Cultural Heritage (ICH), Bida’i. Songket Sambas, Betang traditional house,Makepung and Tektekan AbstrakTujuan penelitian kebijakan Warisan Budaya Takbenda (WBTB) ini, adalah untuk: (1)mengetahui proses dan berbagai masalah dalam implementasi kebijakanWBTB Indonesia;(2) mengidentifikasi pihak-pihak yang terlibat dalam kebijakan WBTB yang telah didaftarkandan ditetapkan; dan (3) mengetahui rencana program aksi yang dilakukan oleh instansi terkaitterhadap penetapan WBTB Indonesia. Penelitian ini menggunakan metode penelitian kualitatifdengan wawancara dan Focus Group Discussion (FGD) terhadap sejumlah informan, baik dariaparat pemerintahan, pelaku budaya, maupun warga masyarakat. Hasil penelitian menunjukanbahwa implementasi Permendikbud yang terkait “prosedur administratif” KebijakanWBTB,telah dilakukan dengan maksimal oleh Direktorat INDB, beserta jajarannya. Meskipun demikian,dalam pelaksanaannya dirasakan kurang maksimal. Hal ini tampaknya, disebabkan kemampuanteknis pengisian formulir maupun pemahaman akan arti budaya takbenda seolah-olah samadengan cagar budaya. Perlu pemahaman dari stakeholders di daerah tentang pentingnya Perpresdan Permendikbud WBTB, sehingga kebijakan ini dapat bergerak bersama di daerah dan salingberkontribusi dalam melakukan perlindungan WBTB dalam bentuk program aksi. Bidai, SongketSambas, dan Rumah Betang di Provinsi Kalimantan Barat, serta Makepung dan Tektekan diProvinsi Bali sudah ditetapkan sebagai WBTB Indonesia. Upaya pelestarian seyogyanya tidakberhenti pada penetapan WBTB tersebut.Kata kunci: Warisan Budaya Takbenda (WBTB), Bidai (Bide’), Songket Sambas, Betang,Makepung dan Tektekan